Oda a Walt Whitman: homenaje de García Lorca al poeta del pueblo y las multitudes - Cuvardic García, Dorde (2006)
An Oda a Walt Whitman is an homage Federico García Lorca to the poet of the masses, of universal love, of democracy. Confronting the dehumanizing city, in this case New York, the poet from Granada yearns for a society of solidarity whose most accessible model is this author of Hojas de hierba. This poem may be interpreted from its generic relevance, the ode, from the question of the apostrophe as used by this United States poet and from the stylistic implications of the representation of the metropolis surrealistically.